PENILAIAN KINERJA KARYAWAN DENGAN MENGGUNAKAN METODE BEHAVIORALLY ANCHOR RATING SCALE DI PENGANDONAN KECAMATAN ULU OGAN KABUPATEN OGAN KOMERING ULU (STUDI KASUS PADA PT. BARUS FAMILLY JAYA) - Nopita Sari; Ervin Mardalena (Jurnal Manajemen Bisnis Unbara, 2021)
This study aims to determine the performance appraisal using the behaviorally anchor rating scale method in Pengandonan, Ulu Ogan District, Ogan Komering Ulu Regency (Case Study at PT. Barus Familly Jaya). Data analysis technique using behaviorally anchor rating scale method. Based on the results of research and processed data, it can be said that employee performance appraisal using the Behaviorally Anchor Rating Scale method can be said from respondents who have been given questionnaires and performance appraisals that have been summed and summed through the employee performance appraisal process are currently effective, with the Behaviorally Anchor method. Rating Scale of employee work behavior can be seen in detail so as to provide an overview of employee performance over a certain period. Currently, employee performance appraisal using the Behaviorally Anchor Rating Scale method can be carried out optimally so that a good employee performance appraisal can be carried out in the future.